Conceptual Evaluation of Brahmacharya as Supreme Rasayana - Saha, Soumyadip; Ray, Sukalyan (International Research Journal of Ayurveda & Yoga, 2025)
Among the three fundamental pursuits of every human being, to live longer has been considered the most primary one. Ayu - “the span of life” depends on proper incorporation of Sharira (physical body), Indriya (sensory organs), Sattva (mind), and Atma (soul), among which Sharira plays the most important role as it hosts the other three factors. The physical body consists of Dosha (functional element), Dhatu (structural element), and Mala (waste portions). To live longer, one needs a sound body and a sound body needs proper regulation and functioning of Doshas and Dhatus. Dhatus are produced within our body from Ahara Rasa by the active participation of Agni. As one former Dhatu partially transforms into the subsequent Dhatu, to maintain the qualitative index of each Dhatu and to achieve more and more optimum Dhatus, proper functioning of Agni is necessary, along with the prevention of erosion within each Dhatu. Ayurvedic texts describe Rasayana as the various ways to achieve Dhatus in their optimal form, which ultimately results in the prevention of senility (Jara Nashanam) along with the alleviation of diseases (Vyadhi Nashanam) as well as other wholesome effects. All these can only be achieved through Rasayana if it is capable of igniting Agni as well as the protection of each Dhatus from erosion. Brahmacharya has been conventionally described as absolute abstinence from sexual activities, although some Ayurvedic scholars considered it as regulated sexual activities. Ayurveda considers Brahmacharya as a type of moral and ethical practice related to social life. Ayurvedic texts refer Brahmacharya as the supreme pathway for achieving longevity of life along with other wholesome effects. For the attainment of such longevity of life, Brahmacharya must act in the same pathway like an ideal Rasayana. The present study conceptually evaluated the wholesome effects of Brahmacharya on our body in line with Rasayana by which it can achieve ignition of Agni and production and sustenance of Dhatus in a more proficient way, which ultimately results in achieving longer life, alleviation of disease, and perfection of body, mind, and intellect.